High-thermal-conductivity ceramic packaging base and production process thereof

By using ceramic slurry composed of modified aluminum nitride and modified carbon nanotubes, combined with conductive layer design, the problem of insufficient thermal conductivity of traditional packaging bases is solved, the high thermal conductivity of ceramic packaging bases is achieved, and the service life of electronic chips is extended.

CN119912266APending Publication Date: 2025-05-02ZHENGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510085036.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The thermal conductivity of traditional packaging bases is insufficient, which makes it difficult for the heat generated by electronic chips to be quickly dispersed, affecting the performance, stability and service life of electronic components.

Method used

The ceramic slurry consisting of modified aluminum nitride and modified carbon nanotubes is used, combined with the design of the conductive layer, and the thermal conductivity of the ceramic packaging base is improved through the preparation method of modified aluminum nitride and the production process of the ceramic packaging base.

Benefits of technology

It significantly improves the thermal conductivity of the ceramic packaging base, and can effectively ensure that the electronic chip is dissipated in time during long-term stable operation, extending its service life.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of electronic packaging, in particular to a high-thermal-conductivity ceramic packaging base and a production process thereof. The high-thermal-conductivity ceramic packaging base comprises a base body and a conductive layer at least arranged on one end face of the base body. The base body is made of ceramic slurry, and the ceramic slurry is prepared from the following raw materials in parts by weight: 50-60 parts of modified aluminum nitride, 0.5-0.8 part of a dispersing agent, 0.6-1.5 parts of a plasticizer, 5-8 parts of a polymer, 35-40 parts of an organic solvent and 1-2 parts of a fluxing agent; the conductive layer is prepared from the following raw materials in parts by weight: 90-96 parts of metal W, 4-7 parts of Al2O3 and 2-5 parts of M2O3; wherein M is any one of Er, Y and Sm; the ceramic packaging base produced by the invention has excellent heat-conducting property, so that the problem that the performance of an electronic component is influenced due to poor heat dissipation of a traditional packaging base is effectively solved to a certain extent, timely heat dissipation of an electronic chip in a long-time stable working process can be ensured, and the service life of the electronic chip is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electronic packaging, and in particular to a high thermal conductivity ceramic packaging base and a production process thereof. Background Art

[0002] With the rapid development of electronic technology, electronic components are constantly moving towards high performance, high integration and miniaturization. In many electronic devices, the packaging base plays a key role in supporting and protecting electronic chips, as well as achieving electrical connections and heat dissipation. Traditional packaging base materials often cannot meet the growing demand for heat dissipation in terms of thermal conductivity. For example, some commonly used plastic packaging bases have low thermal conductivity, which makes it difficult for the heat generated by electronic chips during operation to be quickly dissipated, thereby affecting the performance, stability and service life of electronic components. Ceramic materials have gradually received more attention in the field of packaging bases due to their advantages such as excellent mechanical properties, chemical stability and certain thermal conductivity. However, the existing ceramic packaging bases still have problems such as thermal conductivity that needs to be further improved. Therefore, it is urgent to develop a ceramic packaging base with high thermal conductivity. Summary of the invention

[0003] The purpose of the present invention is to provide a high thermal conductivity ceramic packaging base and its production process. The produced ceramic packaging base has excellent thermal conductivity, which to a certain extent effectively solves the problem that the traditional packaging base affects the performance of electronic components due to poor heat dissipation, and can ensure that the electronic chip dissipates heat in time during long-term stable operation, thereby extending its service life.

[0004] To achieve the above object, the present invention provides the following technical solutions:

[0005] A high thermal conductivity ceramic package base, comprising a base body and a conductive layer at least arranged on one end surface thereof; the base body is made of ceramic slurry, and the ceramic slurry is composed of the following raw materials by weight: 50-60 parts of modified aluminum nitride, 0.5-0.8 parts of dispersant, 0.6-1.5 parts of plasticizer, 5-8 parts of polymer, 35-40 parts of organic solvent and 1-2 parts of flux;

[0006] The conductive material used in the conductive layer is composed of the following raw materials by weight: 90-96 parts of metal W, 4-7 parts of Al 2 O 3 and 2 to 5 portions of M 2 O 3 ; Wherein, M is any one of Er, Y, and Sm.

[0007] Furthermore, the preparation method of the modified aluminum nitride is as follows: pretreated aluminum nitride is added into N,N-dimethylformamide at a dosage ratio of 20 to 50 g / L, and then modified carbon nanotubes with a mass of 0.2 to 0.5 times that of the pretreated aluminum nitride and N,N-diethylethylamine with a volume of 3 to 5% of N,N-dimethylformamide are added, and after ultrasonic dispersion, the resulting mixed solution is placed in an oil bath environment at 110 to 120° C., and stirred for reaction for 5 to 8 hours under the protection of nitrogen; after the reaction is completed, the resulting product components are naturally cooled to room temperature, and then successively subjected to reduced pressure distillation, washing, suction filtration and drying treatment to obtain modified aluminum nitride.

[0008] Furthermore, the preparation method of the pretreated aluminum nitride is as follows: aluminum nitride with a particle size of 2 to 5 μm is added into an ethanol aqueous solution with a volume concentration of 75 to 85% and a pH of 3.8 to 4.5 at a solid-liquid ratio of 10 to 30 g / L, and after mixing and stirring, 3-(2,3-epoxypropoxy)propyltrimethoxysilane with a mass of 0.3 to 0.6 times that of the aluminum nitride is added, and after ultrasonic dispersion for 20 to 30 minutes, the temperature of the obtained dispersion is raised to 60 to 70° C., and the reaction is kept at this temperature for 2 to 5 hours; after the reaction is completed, the product components are separated into solid and liquid, and the filter cake is washed and dried to obtain the pretreated aluminum nitride.

[0009] Furthermore, the preparation method of the modified carbon nanotubes is: immersing the multi-walled carbon nanotubes in a mixed acid solution prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1 at a solid-liquid ratio of 5 to 10 g / L, ultrasonically dispersing for 20 to 30 minutes, and then stirring and reacting at a temperature of 75 to 85°C for 5 to 8 hours; after the reaction is completed, filtering the obtained reaction product, washing the obtained filter cake with water to neutrality and then vacuum drying, and the obtained is the modified carbon nanotubes.

[0010] Furthermore, the dispersant is selected from any one of glycerol, sodium polyacrylate, polysorbate 80, polyethylene glycol, and polyvinyl pyrrolidone.

[0011] Furthermore, the plasticizer is selected from any one of epoxy butyl stearate, trioctyl trimellitate, and phthalate.

[0012] Furthermore, the polymer is selected from any one of polyvinyl butyral, polyacrylate, polymethyl methacrylate, and polyvinyl alcohol.

[0013] Furthermore, the organic solvent is selected from any one of toluene, xylene, butanone and isopropanol.

[0014] Furthermore, the flux is selected from any one of dysprosium oxide, cerium oxide, yttrium oxide and boron nitride.

[0015] A production process of a high thermal conductivity ceramic packaging base comprises the following steps:

[0016] Step 1, mixing and stirring the ceramic slurry evenly, and performing tape casting and curing treatment after degassing to obtain a green ceramic tape;

[0017] Step 2: The obtained green porcelain tape is sliced ​​by a cutting machine to obtain green porcelain sheets, and then the green porcelain sheets are punched and formed by a punching machine or a laser punching machine;

[0018] Step 3: According to the pattern requirements of the conductive layer, the green ceramic sheets after punching are filled with conductive raw materials and printed; the printed green ceramic sheets are placed in a compact stacking mold in accordance with the pre-designed number of layers and order, and stacked to obtain a package base green body; then the package base green body is subjected to isostatic pressing, hot cutting and binder removal sintering in turn to obtain a metallized ceramic;

[0019] Step 5: The metallized ceramic is processed by nickel plating, brazing, gold plating, cleaning, infrared drying, welding, packaging and testing packaging in sequence to obtain a high thermal conductivity ceramic packaging base.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The present invention uses a mixed acid solution prepared by mixing concentrated sulfuric acid and concentrated nitric acid to modify multi-walled carbon nanotubes, so that they are carboxylated to obtain modified carbon nanotubes. Furthermore, the present invention also puts aluminum nitride into an ethanol aqueous solution, and adds 3-(2,3-epoxypropoxy)propyltrimethoxysilane, and after ultrasonic dispersion, 3-(2,3-epoxypropoxy)propyltrimethoxysilane reacts with related groups on the surface of aluminum nitride through a chemical reaction, and finally grafts on the surface of aluminum nitride to obtain pretreated aluminum nitride.

[0022] The obtained pretreated aluminum nitride is put into N,N-dimethylformamide, and modified carbon nanotubes and N,N-diethylethylamine are added thereto. Under the action of N,N-diethylethylamine, the relevant groups on the modified carbon nanotubes react chemically with the pretreated aluminum nitride, and finally the modified carbon nanotubes are effectively grafted on the surface of the pretreated aluminum nitride by bonding to obtain modified aluminum nitride. Since the modified aluminum nitride is made of a mixture of aluminum nitride and carbon nanotubes, the produced modified aluminum nitride has excellent thermal conductivity. Using the modified aluminum nitride as a raw material for a ceramic packaging base can effectively improve its thermal conductivity, which effectively solves the problem that the performance of electronic components is affected by poor heat dissipation of the traditional packaging base to a certain extent, and can ensure that the electronic chip dissipates heat in time during long-term stable operation, thereby extending its service life. DETAILED DESCRIPTION

[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Example 1

[0025] A high thermal conductivity ceramic packaging base, comprising a base body and a conductive layer at least arranged on one end surface thereof; the base body is made of ceramic slurry, and the ceramic slurry is composed of the following raw materials in parts by weight: 50 parts of modified aluminum nitride, 0.5 parts of propylene glycol, 0.6 parts of epoxy stearate butyl, 5 parts of polyvinyl butyral, 35 parts of toluene and 1 part of dysprosium oxide;

[0026] The conductive material used in the conductive layer is composed of the following raw materials by weight: 90 parts of metal W, 4 parts of Al 2 O 3 and 2 parts of Er 2 O 3 .

[0027] The preparation method of modified aluminum nitride is as follows: pretreated aluminum nitride is added into N,N-dimethylformamide at a dosage ratio of 20g / L, and then modified carbon nanotubes with a mass 0.2 times that of the pretreated aluminum nitride and N,N-diethylethylamine with a volume of 3% of N,N-dimethylformamide are added, and after ultrasonic dispersion, the obtained mixed solution is placed in an oil bath environment at 110°C, and stirred for reaction for 8 hours under the protection of nitrogen; after the reaction is completed, the obtained product components are naturally cooled to room temperature, and then successively subjected to reduced pressure distillation, washing, suction filtration and drying treatment to obtain modified aluminum nitride.

[0028] The preparation method of pretreated aluminum nitride is as follows: aluminum nitride with a particle size of 2 μm is put into an ethanol aqueous solution with a volume concentration of 75% and a pH of 3.8 at a solid-liquid ratio of 10 g / L, and after mixing and stirring, 3-(2,3-epoxypropoxy)propyltrimethoxysilane with a mass of 0.3 times that of aluminum nitride is added, and after ultrasonic dispersion for 20 minutes, the temperature of the obtained dispersion is raised to 60°C, and the reaction is kept at this temperature for 5 hours; after the reaction is completed, the product components are separated into solid and liquid, and the filter cake is washed and dried to obtain the pretreated aluminum nitride.

[0029] The preparation method of modified carbon nanotubes is as follows: multi-walled carbon nanotubes are immersed in a mixed acid solution prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1 at a solid-liquid ratio of 5g / L, and then ultrasonically dispersed for 20 minutes and stirred at a temperature of 75°C for 8 hours; after the reaction is completed, the reaction product is filtered, the filter cake is washed with water to neutrality and then vacuum dried to obtain the modified carbon nanotubes.

[0030] A production process of a high thermal conductivity ceramic packaging base comprises the following steps:

[0031] Step 1, mixing and stirring the ceramic slurry evenly, and performing tape casting and curing treatment after degassing to obtain a green ceramic tape;

[0032] Step 2: The obtained green porcelain tape is sliced ​​by a cutting machine to obtain green porcelain sheets, and then the green porcelain sheets are punched and formed by a punching machine or a laser punching machine;

[0033] Step 3: According to the pattern requirements of the conductive layer, the green ceramic sheets after punching are filled with conductive raw materials and printed; the printed green ceramic sheets are placed in a compact stacking mold in accordance with the pre-designed number of layers and order, and stacked to obtain a package base green body; then the package base green body is subjected to isostatic pressing, hot cutting and binder removal sintering in turn to obtain a metallized ceramic;

[0034] Step 5: The metallized ceramic is processed by nickel plating, brazing, gold plating, cleaning, infrared drying, welding, packaging and testing packaging in sequence to obtain a high thermal conductivity ceramic packaging base.

[0035] Example 2

[0036] The production process of a high thermal conductivity ceramic package base provided in this embodiment is basically the same as that in Example 1, except that: the specific composition of the ceramic slurry and the conductive raw material used in the high thermal conductivity ceramic package base and the preparation method of the modified aluminum nitride are not completely the same. The specific composition of the ceramic slurry and the conductive raw material used in the high thermal conductivity ceramic package base and the preparation method of the modified aluminum nitride in this embodiment are as follows:

[0037] A high thermal conductivity ceramic packaging base, comprising a base body and a conductive layer at least arranged on one end surface thereof; the base body is made of ceramic slurry, and the ceramic slurry is composed of the following raw materials in parts by weight: 55 parts of modified aluminum nitride, 0.6 parts of sodium polyacrylate, 1 part of trioctyl trimellitate, 6 parts of polyacrylate, 40 parts of xylene and 1.5 parts of cerium oxide;

[0038] The conductive material used in the conductive layer is composed of the following raw materials by weight: 93 parts of metal W, 5 parts of Al 2 O 3 and 3 parts Y 2 O 3 .

[0039] The preparation method of modified aluminum nitride is as follows: pretreated aluminum nitride is added into N,N-dimethylformamide at a dosage ratio of 30g / L, and then modified carbon nanotubes with a mass 0.3 times that of the pretreated aluminum nitride and N,N-diethylethylamine with a volume of 4% of N,N-dimethylformamide are added, and after ultrasonic dispersion, the obtained mixed solution is placed in an oil bath environment at 115°C, and stirred for reaction for 6 hours under the protection of nitrogen; after the reaction is completed, the obtained product components are naturally cooled to room temperature, and then successively subjected to reduced pressure distillation, washing, suction filtration and drying treatment to obtain modified aluminum nitride.

[0040] The preparation method of pretreated aluminum nitride is as follows: aluminum nitride with a particle size of 3 μm is put into an ethanol aqueous solution with a volume concentration of 80% and a pH of 4.0 at a solid-liquid ratio of 20 g / L, and after mixing and stirring, 3-(2,3-epoxypropoxy)propyltrimethoxysilane with a mass of 0.5 times that of aluminum nitride is added, and after ultrasonic dispersion for 25 minutes, the temperature of the obtained dispersion is raised to 65°C, and the reaction is kept at this temperature for 3 hours; after the reaction is completed, the product components are separated into solid and liquid, and the filter cake is washed and dried to obtain the pretreated aluminum nitride.

[0041] The preparation method of modified carbon nanotubes is as follows: multi-walled carbon nanotubes are immersed in a mixed acid solution prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1 at a solid-liquid ratio of 10g / L, and then ultrasonically dispersed for 25 minutes and stirred at a temperature of 80°C for 6 hours; after the reaction is completed, the reaction product is filtered, the filter cake is washed with water to neutrality and then vacuum dried to obtain the modified carbon nanotubes.

[0042] Example 3

[0043] The production process of a high thermal conductivity ceramic package base provided in this embodiment is basically the same as that in Example 1, except that: the specific composition of the ceramic slurry and the conductive raw material used in the high thermal conductivity ceramic package base and the preparation method of the modified aluminum nitride are not completely the same. The specific composition of the ceramic slurry and the conductive raw material used in the high thermal conductivity ceramic package base and the preparation method of the modified aluminum nitride in this embodiment are as follows:

[0044] A high thermal conductivity ceramic packaging base, comprising a base body and a conductive layer at least arranged on one end surface thereof; the base body is made of ceramic slurry, and the ceramic slurry is composed of the following raw materials in parts by weight: 60 parts of modified aluminum nitride, 0.8 parts of polysorbate-80, 1.5 parts of phthalate, 8 parts of polymethyl methacrylate, 40 parts of isopropyl alcohol and 2 parts of yttrium oxide;

[0045] The conductive material used in the conductive layer is composed of the following raw materials by weight: 96 parts of metal W, 7 parts of Al 2 O 3 and 5 parts Sm 2 O 3 .

[0046] The preparation method of modified aluminum nitride is as follows: pretreated aluminum nitride is added into N,N-dimethylformamide at a dosage ratio of 50g / L, and then modified carbon nanotubes with a mass 0.5 times that of the pretreated aluminum nitride and N,N-diethylethylamine with a volume of 5% of N,N-dimethylformamide are added, and after ultrasonic dispersion, the obtained mixed solution is placed in an oil bath environment at 120°C, and stirred for reaction for 5 hours under the protection of nitrogen; after the reaction is completed, the obtained product components are naturally cooled to room temperature, and then successively subjected to reduced pressure distillation, washing, suction filtration and drying treatment to obtain modified aluminum nitride.

[0047] The preparation method of pretreated aluminum nitride is as follows: aluminum nitride with a particle size of 5 μm is put into an ethanol aqueous solution with a volume concentration of 85% and a pH of 4.5 at a solid-liquid ratio of 30 g / L, and after mixing and stirring, 3-(2,3-epoxypropoxy)propyltrimethoxysilane with a mass of 0.6 times that of aluminum nitride is added, and after ultrasonic dispersion for 30 minutes, the temperature of the obtained dispersion is raised to 70°C, and the reaction is kept at this temperature for 2 hours; after the reaction is completed, the product components are separated into solid and liquid, and the filter cake is washed and dried to obtain the pretreated aluminum nitride.

[0048] The preparation method of modified carbon nanotubes is as follows: multi-walled carbon nanotubes are immersed in a mixed acid solution prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1 at a solid-liquid ratio of 10g / L, and then ultrasonically dispersed for 30 minutes and stirred at a temperature of 85°C for 5 hours; after the reaction is completed, the reaction product is filtered, the filter cake is washed with water to neutrality and then vacuum dried to obtain the modified carbon nanotubes.

[0049] The difference between the comparative example and the present embodiment and embodiment 1 is that in the present embodiment, aluminum nitride with an equal particle size of 2 μm is used instead of modified aluminum nitride.

[0050] Performance test: The relevant performances of the high thermal conductivity ceramic package base samples produced in Examples 1 to 3 and the comparative example were tested respectively, and the obtained test data were recorded in the following table:

[0051] Test items Binding force / N Thermal conductivity (W / m·K) Wiring resistance / Ω Whether the conductive layer collapses or bulges Example 1 52.2 188 0.11 none Example 2 52.6 195 0.08 none Example 3 51.9 192 0.09 none Comparative Example 46.9 176 0.21 none

[0052] By comparing and analyzing the relevant data in the table, it can be seen that the ceramic package base produced by the present invention has excellent thermal conductivity, which effectively solves the problem that the traditional package base has poor heat dissipation, thereby affecting the performance of electronic components, and can ensure that the electronic chip dissipates heat in a timely manner during long-term stable operation, thereby extending its service life. This shows that the high thermal conductivity ceramic package base and its preparation method provided by the present invention have a broader market prospect and are more suitable for promotion.

[0053] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0054] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A high thermal conductivity ceramic package base, comprising a base body and a conductive layer disposed at least on one end surface thereof; characterized in that: The base body is made of ceramic slurry, and the ceramic slurry is composed of the following raw materials by weight: 50-60 parts of modified aluminum nitride, 0.5-0.8 parts of dispersant, 0.6-1.5 parts of plasticizer, 5-8 parts of polymer, 35-40 parts of organic solvent and 1-2 parts of flux; The conductive raw material used for the conductive layer is composed of the following raw materials by weight: 90 to 96 parts of metal W, 4 to 7 parts of Al2O3 and 2 to 5 parts of M2O3; wherein M is any one of Er, Y and Sm.

2. The high thermal conductivity ceramic package base according to claim 1, characterized in that: The preparation method of the modified aluminum nitride is as follows: pretreated aluminum nitride is added into N,N-dimethylformamide at a dosage ratio of 20-50 g / L, and then modified carbon nanotubes with a mass of 0.2-0.5 times that of the pretreated aluminum nitride and N,N-diethylethylamine with a volume of 3-5% of that of the N,N-dimethylformamide are added, and after ultrasonic dispersion, the obtained mixed solution is placed in an oil bath environment at 110-120° C., and stirred and reacted for 5-8 hours under the protection of nitrogen; after the reaction is completed, the obtained product components are naturally cooled to room temperature, and then subjected to reduced pressure distillation, washing, suction filtration and drying treatment in sequence to obtain the modified aluminum nitride.

3. The high thermal conductivity ceramic package base according to claim 2, characterized in that: The preparation method of the pretreated aluminum nitride is as follows: aluminum nitride with a particle size of 2 to 5 μm is added into an ethanol aqueous solution with a volume concentration of 75 to 85% and a pH of 3.8 to 4.5 at a solid-liquid ratio of 10 to 30 g / L, 3-(2,3-epoxypropoxy)propyltrimethoxysilane with a mass of 0.3 to 0.6 times that of the aluminum nitride is added after mixing and stirring, and the temperature of the obtained dispersion is raised to 60 to 70° C. after ultrasonic dispersion for 20 to 30 minutes, and the dispersion is kept at this temperature for reaction for 2 to 5 hours; after the reaction is completed, the resultant components are separated into solid and liquid, and the filter cake is washed and dried to obtain the pretreated aluminum nitride.

4. The high thermal conductivity ceramic package base according to claim 2, characterized in that: The preparation method of the modified carbon nanotubes is as follows: immersing multi-walled carbon nanotubes in a mixed acid solution prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1 at a solid-liquid ratio of 5-10 g / L, ultrasonically dispersing for 20-30 minutes, and then stirring and reacting at a temperature of 75-85° C. for 5-8 hours; after the reaction is completed, filtering the obtained reaction product, washing the obtained filter cake with water until it is neutral, and then vacuum drying, and the obtained modified carbon nanotubes are obtained.

5. The high thermal conductivity ceramic package base according to claim 1, characterized in that: The dispersant is selected from any one of glycerol, sodium polyacrylate, polysorbate-80, polyethylene glycol, and polyvinyl pyrrolidone.

6. The high thermal conductivity ceramic package base according to claim 1, characterized in that: The plasticizer is selected from any one of epoxy butyl stearate, trioctyl trimellitate and phthalate.

7. The high thermal conductivity ceramic package base according to claim 1, characterized in that: The polymer is selected from any one of polyvinyl butyral, polyacrylate, polymethyl methacrylate and polyvinyl alcohol.

8. The high thermal conductivity ceramic package base according to claim 1, characterized in that: The organic solvent is selected from any one of toluene, xylene, butanone and isopropanol.

9. The high thermal conductivity ceramic package base according to claim 1, characterized in that: The flux is selected from any one of dysprosium oxide, cerium oxide, yttrium oxide and boron nitride.

10. A production process for a high thermal conductivity ceramic package base according to any one of claims 1 to 9, characterized in that: The following steps are involved: Step 1, mixing and stirring the ceramic slurry evenly, and performing tape casting and curing treatment after degassing to obtain a green ceramic tape; Step 2: The obtained green porcelain tape is sliced ​​by a cutting machine to obtain green porcelain sheets, and then the green porcelain sheets are punched and formed by a punching machine or a laser punching machine; Step 3: According to the pattern requirements of the conductive layer, the green ceramic sheets after punching are filled with conductive raw materials and printed; the printed green ceramic sheets are placed in a compact stacking mold in accordance with the pre-designed number of layers and order, and stacked to obtain a package base green body; then the package base green body is subjected to isostatic pressing, hot cutting and binder removal sintering in turn to obtain a metallized ceramic; Step 5: The metallized ceramic is processed by nickel plating, brazing, gold plating, cleaning, infrared drying, welding, packaging and testing packaging in sequence to obtain a high thermal conductivity ceramic packaging base.